Sosialisasi Lintas Sektor dalam Upaya Pencegahan Stunting di Kabupaten Mamuju - Najdah Najdah; Adriyani Adam; Nurliah Nurliah; Nurbaya Nurbaya (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Efforts to improve the nutritional status of families are not only by improving the quality of health services but also need to be accompanied by efforts to empower families towards independence. In general, obstacles to implementing stunting prevention in Indonesia are caused by weak program coordination at various levels, both the regional and central levels. This activity aimed to conduct cross-sectoral socialization and increase public knowledge about efforts to prevent stinting in community empowerment. The main targets of this activity are stakeholders across sectors and mothers of children under five. The method used is socialization, lectures, and discussions as well as demonstrations of making local MP-ASI. Participants across sectors were enthusiastic in the discussion and question-and-answer process. Participants from mothers of toddlers were able to demonstrate the manufacture of local MP-ASI. Stunting consultations at the village level need to be encouraged so that stunting prevention efforts can be carried out in synergy. ABSTRAK Upaya meningkatkan status gizi keluarga tidak hanya dengan meningkatkan mutu pelayanan kesehatan, tetapi juga perlu dibarengi dengan upaya pemberdayaan keluarga menuju kemandirian. Secara umum kendala dalam penyelenggaraan pencegahan stunting di Indonesia diakibatkan oleh lemahnya koordinasi program di berbagai tingkat baik di daerah maupun di tingkat pusat. Kegiatan ini bertujuan untuk melakukan sosialisasi lintas sektor dan peningkatan pengetahuan masyarakat tentang upaya pencegahan stunting pemberdayaan masyarakat. Sasaran utama kegiatan ini para stakeholder lintas sektor dan ibu balita. Metode yang digunakan adalah sosialisasi, ceramah dan diskusi serta demonstrasi pembuatan MP-ASI lokal. Peserta lintas sektor antusias dalam proses diskusi dan tanya jawab. Peserta dari kalangan ibu balita mampu mendemonstrasikan pembuatan MP-ASI lokal. Rembuk stunting di tingkat desa perlu digalakkan agar upaya pencegahan stunting dapat dilakukan secara bersinergi.